2006
DOI: 10.1039/b609879g
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of proteins with linear polyelectrolytes and spherical polyelectrolyte brushes in aqueous solution

Abstract: We review recent experiments on the interaction of proteins with anionic polyelectrolytes in aqueous solution. Data from the literature demonstrate that proteins can form soluble complexes with linear polyelectrolytes even on the "wrong side" of the isoelectric point, that is, for pH values above the isoelectric point of the proteins under which the polyelectrolytes and the proteins are like-charged. All data published so far demonstrate that this type of adsorption becomes weaker with increasing ionic strengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
277
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(290 citation statements)
references
References 54 publications
(180 reference statements)
11
277
0
2
Order By: Relevance
“…This is due to the intrinsic amphiphilic character of the protein that facilitated the adsorption of protein onto similarly charged surfaces. 36 Hence, although the net charge of a protein is negative, positively charged patches on the protein surface are also present due to the heterogeneous distribution on the protein surface. 37,38 Park et al demonstrated positive charge patches in bovine serum albumin (BSA) (that is otherwise negatively charged), 39 allowing BSA to bind with a strong polyanion, as also observed in this work and in a previous report.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the intrinsic amphiphilic character of the protein that facilitated the adsorption of protein onto similarly charged surfaces. 36 Hence, although the net charge of a protein is negative, positively charged patches on the protein surface are also present due to the heterogeneous distribution on the protein surface. 37,38 Park et al demonstrated positive charge patches in bovine serum albumin (BSA) (that is otherwise negatively charged), 39 allowing BSA to bind with a strong polyanion, as also observed in this work and in a previous report.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…32,38 The protein could also carry multiple positive charges and therefore be able to replace the counterions on a polymer surface. 32,36 In addition, albumin can also bind to the hydrophobic site of polymethacrylic acid. The binding between albumin and a hydrophobic surface is often used as a protein carrier for hydrophobic molecules, such as drugs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Because of their complex structure proteins typically exhibit different affinities in different regions of their surface depending on the local composition of amino acid residues. An often applied concept is to divide the protein's surface into different patches or domains that can be of hydrophobic, hydrophilic, positively, or negatively charged nature [84][85][86]. Thus, on hydrophilic interfaces proteins predominantly expose those patches toward the surface that are rich of hydrophilic residues and on hydrophobic surfaces proteins direct their hydrophobic patches to the surface.…”
Section: Side-on or End-on? The Protein's Orientationmentioning
confidence: 99%
“…Moreover, the biological activity of the bound and redesorbed proteins and enzymes is nearly the same as in the native state [12]. Hence, spherical polyelectrolyte brushes present a well-defined model system for the study of protein adsorption [12].BSA solutions (15 g=l; Sigma A6003; Lot. : 045K7422) were prepared in a MES-buffer (2-N-morpholinoethane sulfonic acid) containing 2 mM NaN 3 to avoid microbial growth.…”
mentioning
confidence: 99%